PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - SUMARNI, RANI; GUSTINA, IRA; NURFITRIANI, NURFITRIANI (JURNAL AKUNTANSI DAN KEUANGAN, 2023)
This research was conducted at banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period with the aim of knowing the effect of liquidity and capital structure on profitability. The research population carried out by researchers is banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample selection was carried out using purposive sampling method, and a sample of 32 companies was obtained. The type of data used is secondary data. Secondary data is data in the form of annual reports obtained from the IDX Website, namely www.idx.co.id during the 2019-2021 period. The data analysis method used in this study is multiple linear regression, with the classical assumption tests used are data normality tests, autocorrelation, multicollinearity, and heteroscedasticity tests. Descriptive statistics are used to see the profile of the research and provide an overview of the object to be studied through sample data and make generally accepted conclusions. The results of this study indicate that the t test (partial test) of liquidity has an effect on profitability. While the capital structure has no effect on profitability. The f test (simultaneous test) can be concluded that the variables of liquidity and capital structure simultaneously affect profitability.